Енергозберігаючий метод синтезу кальційфосфатних матеріалів біомедичного призначення, армованих монокристалами - Бережний, А. С.; Кривiльова, С. П. (Національний технічний університет "Харківський політехнічний інститут", 2017)
Встатье рассмотрен энергосберегающий метод получения кальцийфосфатных материалов биомедицинского назначения, армированных монокристаллами, синтез которых осуществляется в кальцийфосфатной матрице в процессе термообработки шихты, состоящей из Са₁₀(PO₄)₆(OH)₂ и стеарата магния Mg(С₁₇H₃₅COO)₂. Изучено влияние условий синтеза на микроструктуру и свойства, определено оптимальное соотношение исходных компонентов и режимі термообработки. Разработанный метод позволяет исключить стадию предварительного синтеза монокристаллов периклаза и сформировать структуру материала без горячего прессования, что способствует существенному снижению энергозатратности его производства.

The article considers an energy-saving method for obtaining calcium phosphate materials of biomedical use, reinforced with single crystals, which are synthesized in the calcium phosphate matrix during heat treatment. The feasibility of synthesizing a ceramic material based on Са₁₀(PO₄)₆(OH)₂, reinforced with periclase single crystals, from a pre-synthesized synthetic hydroxyapatite Са₁₀(PO₄)₆(OH)₂, and magnesium stearate Mg(С₁₇H₃₅COO)₂ was evaluated. Nanocrystalline synthetic hydroxyapatite Са₁₀(PO₄)₆(OH)₂ was synthesized from aqueous solutions of Са(OH)₂ and Н₃PO₄. Optimal compositions and modes of heat treatment are determined. The developed method allows to exclude the stage of preliminary synthesis of periclase single crystals and to form the structure of the material without hot pressing, which contributes to a significant reduction in the energy cost of its production.
Energy-saving synthes of calcium-phosphate materials of biomedical purpose, reinforced with monocrystals
Keywords: керамічна галузь; кераміко-металеві композити; біокерамічні матеріали; кістково-суглобова система; механічне навантаження